A Study of Some Predictors of Anaemia in Children of Under-Five Years in India - Goswami, Sankar; Das, Kishore K (Asian Journal of Medical Sciences, 2013)
Background: The major nutritional problem among young children in India is anaemia that affects the ability to study and work and is significantly associated with increased morbidity and mortality. Objectives: To analyze the prevalence of anaemia among Indian children of underfive years and to identify the significant risk factors associated with it. Methods: Data of 35851 children from NFHS-III, India were analyzed and binary logistic regression model was fitted by using SPSS 15.0 software. Anaemia was defined as haemoglobin concentration level below 11 g/dl. HemoCue Hb 201+ analyzer was used to measure haemoglobin concentration. Results: Overall, 69.5 percent were anaemic with the highest proportion in Bihar and the least in Goa. The age and birth order of child; religion, caste and wealth index of household; anaemia level, education, age at first birth, intake of iron supplements during pregnancy and vegetarian habit of mother showed significant influence on child anaemia. Conclusion: Child anaemia prevails significantly in India and the findings suggest for urgent prevention and treatment measures giving importance to the different socioeconomic characteristics. DOI: http://dx.doi.org/10.3126/ajms.v5i2.8508 Asian Journal of Medical Science, Volume-5(2) 2014: 26-32